Maintenance Training for Sustainability Maintaining Solar Power in Andamata Village: Pelatihan Perawatan untuk Menjaga Keberlanjutan Pembangkit Listrik Tenaga Surya di Kampung Andamata - Rusliadi, Rusliadi; La Elo, Yulianto; Prastoro, Wiko; Husnah, Nurul; HR, Herman; Lembang, Naomi; Syamsul, Muhammad Ayyub (Politeknik Negeri Fakfak, 2025)
Fakfak Regency is one of the areas in the West Papua region consisting of a cluster of islands and Andamata Village is one of the clusters of islands with a location far from the city center of Fakfak Regency. With such geographical conditions, it is a challenge for the local government, especially PLN, to be able to distribute electrical energy properly. However, PLN as the main supplier of national energy has made developments by implementing solar power plants for areas far from the city center of Fakfak. However, to maintain the sustainability of this power plant, experts are needed who can carry out maintenance and care on the solar power plant system. Therefore, this community service activity is carried out to train local communities and youth leaders to be able to carry out maintenance and early response if there is a problem with the PLTS system. The method used in this activity is to provide material on PLTS system maintenance, carry out system maintenance practices and evaluations. Based on the results of the evaluation, the community's understanding and skills in maintaining the PLTS system are classified as very good. This can be seen from the level of understanding of participants, the average very understanding reached 28%, the understanding category with an average of 60%, the fairly understanding category with an average of 10% and the average category of not understanding reached 2%.